КОРРУПЦИЯГА ҚАРШИ КУРАШ – ҒОЯВИЙ ТАРБИЯНИНГ АСОСИЙ МЕЗОНИ СИФАТИДА - Қадиров, Қ.А. (SCIENCE and SOCIETY, 2021)
This article is devoted to state policy, ongoing reforms, the factors that generate this corruption, and issues aimed at preventing it in the new Uzbekistan, both in the world community and in our republic.